2022
DOI: 10.1002/kjm2.12546
|View full text |Cite
|
Sign up to set email alerts
|

MFAP2 aggravates tumor progression through activating FOXM1/β‐catenin‐mediated glycolysis in ovarian cancer

Abstract: Ovarian cancer is one of the most common gynecological tumors that seriously endanger the health and quality of life of women. Microfibril‐associated protein 2 (MFAP2) has been demonstrated to play crucial roles in the development of multiple tumors. However, the function of MFAP2 in ovarian cancer remains unclear. In this study, we found that MFAP2 was upregulated in ovarian cancer and cells and was positively correlated with FOXM1 and glycolysis‐related genes. The results of Cell Count Kit‐8, colony formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…CENPA, as the target of FOXM1, has shown the regulation of FOXM1/CENPA in pancreatic β-cell proliferation. 15,45 Here, this study first provides evidence supporting the fact that FOXM1 induced CENPA expression by directly binding to its promoter and subsequently promoted TNBC progression and glycolysis.…”
Section: Discussionmentioning
confidence: 54%
“…CENPA, as the target of FOXM1, has shown the regulation of FOXM1/CENPA in pancreatic β-cell proliferation. 15,45 Here, this study first provides evidence supporting the fact that FOXM1 induced CENPA expression by directly binding to its promoter and subsequently promoted TNBC progression and glycolysis.…”
Section: Discussionmentioning
confidence: 54%
“…It was found that its expression in tumor tissues was significantly higher than that in normal tissues ( 33 ). The MFAP2 mRNA and protein levels in all ovarian cancer cell lines were much higher than those in non-tumor IOSE80 cell lines ( 18 ). In colorectal adenocarcinoma, the MFAP2 mRNA expression in tumor tissues was significantly higher than that in the adjacent non-tumor tissues.…”
Section: The Expression Of Mfap2 In Tumorsmentioning
confidence: 81%
“…Similarly, MFAP2 overexpression reduced G1 phase cell proportion and increased those of S and G2/M phase cells in ovarian cancer, suggesting that MFAP2 could stimulate G1-S phase cell transition. In contrast, MFAP2 knockdown induced significant arrest in the G0/G1 phase and decreased the S and G2/M phase cell proportion, indicating that cell cycle processes are affected ( 18 ). These data showed that MFAP2 promotes tumor cell proliferation through numerous mechanisms.…”
Section: The Carcinogenic Effect Of Mfap2 and Its Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations